Karakteristik Adonan dan Roti Tawar dengan Penambahan Enzim dan Asam Askorbat pada Tepung Terigu - Agus Sutriyono; Feri Kusnandar; Tjahja Muhandri (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
Wheat flour containing a 33-39% wet gluten is commonly applied in pan bread processing, however, it is expensive. The use of wheat flour containing a lower wet gluten yields a lower quality bread. This objective of this research was to produce acceptable quality pan bread using enzyme-treated wheat flour containing medium wet gluten content (31.8%). Wheat flour was treated by adding enzymes and ascorbic acid. The combination of enzymes (30 ppm α-amylase, 26 ppm α-glucosidase, 16 ppm xylanase), and 40 ppm ascorbic acid yielded dough resistancy and extensibility as well as the bread qua-lity that miccked those made of high wet gluten wheat flour (35.0%).